Cameron Center Springs Restaurant Interior - Seating and Wall Tiling - Erwin Lang::::::photographer:::
Interior photo of the Huddle Springs Restaurant in the Cameron Center featuring seating by a wall tiled with tribal motifs. The mosaic is by Millard Sheets.